(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the recovery quality between Desflurane and Sevoflurane in pediatric patients undergoing laparoscopic abdominal surgery. Subjects and methods: A randomized clinical trial was conducted on 60 children aged 6-12 years, divided into two groups: Desflurane (n = 30) and Sevoflurane (n = 30). Mean arterial pressure (MAP), heart rate, time to spontaneous breathing, eye opening, extubation, and MAC dynamics (mean MAC during maintenance; time to reach MAC 0.5 and 0.2) were recorded. Data were analyzed with a significance level of p < 0.05. Results: Baseline characteristics were comparable between the 2 groups (p > 0.05). Mean arterial pressure remained stable without significant differences; heart rate was slightly higher in the Desflurane group but within physiological limits (p < 0.05). The mean maintenance MAC was similar (0.78 ± 0.07 vs. 0.76 ± 0.10; p = 0.460), but the times to reach MAC 0.5 and 0.2 were significantly shorter in the Desflurane group (p < 0.001). Recovery times were faster with Desflurane than with Sevoflurane: spontaneous breathing 9.53 ± 1.17 minutes vs. 16.17 ± 1.74 minutes; eye opening 14.97 ± 1.47 minutes vs. 24.87 ± 1.36 minutes; extubation 22.07 ± 1.31 minutes vs. 31.83 ± 1.46 minutes (p < 0.001). Conclusion: Desflurane provides faster recovery than Sevoflurane, maintains stable hemodynamics, and demonstrates favorable MAC kinetics (faster decline to MAC 0.5 and 0.2).